Evaluation of D-Dimer Levels in Various Subgroups of Atrial Fibrillation: Role in Risk Stratification - Mani, Avinash; Ojha, Vineeta; Sinha, Pradip Kumar; Saha, Jayanta (Cardiology and Cardiovascular Medicine, 2022)
Background: D-dimer levels have been shown to be elevated in atrial fibrillation(AF) patients. However, different subgroups of AF have not been evaluated. We aimed to evaluate D-dimer levels in different subgroups of AF and determine association between D-dimer levels and adverse outcomes like heart failure and thromboembolism. Methods: This was a single center, cross sectional, observational study which included patients with AF treated at a tertiary care hospital, from January 2017 to December 2017. Patients were subdivided into different subgroups based on etiology and D-dimer levels were measured. Reference value for the normal population was taken as < 0.5 μg/ml. Results: 70 patients with AF were studied over a one-year period. Mean age of study population was 53 years. Valvular AF was the most common etiology(30%) noted followed by non-ischemic cardiomyopathy (NICM) (14.2%). About half of study population had history of heart failure whereas thromboembolism(TE) was noted in 15.7%. 72.8% patients had elevated D-dimer levels in the cohort. D-dimer levels were significantly higher in valvular AF(1.2 μg/ml) and NICM patients(1.4 μg/ml) (p=0.005). Higher D-dimer levels were noted in those with heart failure (HF) events (p=0.016). D-dimer levels were shown to accurately detect prior HF/ TE events with levels of 1.1 μg/ml and higher having a sensitivity and specificity of 59.1% and 81%, respectively (AUC 0.727). Conclusion: D-dimer levels are significantly higher in valvular AF and NICM patients. D-dimer levels have a strong association with HF/TE events and elevated levels can be used to detect at risk patients.